2014
DOI: 10.1017/s1463423614000024
|View full text |Cite
|
Sign up to set email alerts
|

A community-based Falls Management Exercise Programme (FaME) improves balance, walking speed and reduced fear of falling

Abstract: The FaME programme improves balance, walking speed and reduces fear of falling. It could be widely promoted and integrated into regular health and social activities in community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Elderly patients with peer support and a sense of belonging favour long-term sustainable rehabilitation, as suggested by Wong's study (13). Compliance with exercise classes and vibration-therapy were 66.1% and 74.9%, respectively, in the present study, which was comparable to previous studies with an adherence rate of 42.3-79% in 12-month community-based programmes (33,34).…”
Section: Cost Analysissupporting
confidence: 87%
“…Elderly patients with peer support and a sense of belonging favour long-term sustainable rehabilitation, as suggested by Wong's study (13). Compliance with exercise classes and vibration-therapy were 66.1% and 74.9%, respectively, in the present study, which was comparable to previous studies with an adherence rate of 42.3-79% in 12-month community-based programmes (33,34).…”
Section: Cost Analysissupporting
confidence: 87%
“…13 In a cohort study of nursing home residents (48 in the intervention group and 51 in the control group) in Hong Kong who underwent a 36-week fall management exercise programme (12 weeks of adaptation to exercise techniques, 12 weeks of coordination exercises, and 12 weeks of balance and walking function exercises), participants were assessed for mental status, fear of falling, avoidance of activities, balance, timed up-and-go test, and history of falls in the past 1 year. 15 The two groups were comparable in terms of the percentage of fallers and the number of falls. The intervention group showed significant improvement in fall risk factors such as the Berg balance scale, the 6-minute walking test, and the falls efficacy scale.…”
Section: Fall Prevention Interventions Exercisementioning
confidence: 91%
“…In a study of residents in six nursing homes in Hong Kong, 26 weeks of Tai Chi was reported to be effective in improving the quality of life of residents. 15 In a study in Taichung, Taiwan, Tai Chi was reported to improve balance but had no effect on reducing the fall rate. 16 The activity level of Tai Chi is equivalent to moderate-intensity exercise; the technique involves no heavy or quick physical movements.…”
Section: Fall Prevention Interventions Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…It was designed to ensure high compliance with the directed exercises. The self-reported factors that motivated elderly people to participate included noted beneficial effects on their activities of daily living with increased capacity to carry out housework and improved walking stability, improved regular and long-term scheduling, a manageable level of difficulty, and a comfortable and friendly environment with a group of peers [27]. Recently, programs for frailty intervention have also started; they have had an excellent response rate despite costing money and, in some cases, requiring long travel times to their locations.…”
Section: Hong Kong As a Case Studymentioning
confidence: 99%